Prinsip-Prinsip Humanisme Menurut Ali Syari'ati - Prawira Negara, Muhammad Adres; Muhlas, Muhlas (Jurnal Riset Agama, 2023)
Islam has universal teachings, namely human values. Ali Shari'ati is one of the Islamic revolutionary thinkers who paid attention to humanism. According to him, humanism is a school of philosophy that views groups that aim to achieve perfection in humans. Ali Shari'ati emphasized that humans are creatures that have various values given by God. Humans are the most unique nature, because humans were created by God as the noblest creatures, have their own freedom, and are not controlled by something, so that humans can determine the direction of their lives freely and be responsible for their choices. This research aims to explore Ali Shariati's thoughts related to the principles of humanism. This research is a literature study that uses a qualitative approach with descriptive-analytic method. The result of this research is that according to Ali Shariati, humans as God's representatives on earth certainly have divine values that form moral, cultural and religious values. Then, in the principle of humanism built by Ali Shari'ati, he explained that there are seven basic concepts in Islamic humanism, including humans having autonomous elements, having freedom, thinking creatures, conscious creatures, creatures that have creativity, creatures that have desires, and creatures that have morals.